Pressure Change in the Chambers of the Hypogerotor Pump Applied in Lubrication of the Combustion Engines - Nguyen, Hong Thai; Truong, Cong Giang (Old Journal, 2019)
Hypogerotor pump is a hydraulic machine based on internal mating gears with hypocycloidal profile. This type of pumps has just been presented in recent time with researching works on condition for profile generation, slippage of the tooth profile, flow rate of the pump etc. In order to determine the change of pressure in pump chambers at arbitrary time during one working period, the numerical methods with finite element analysis have usually been used. On the other hand, the analytical method using the line of action and the characteristic design parameters has never been presented. In this paper, the authors combine Bernoulli’s principle with gearing theory of hypocycloidal gears to propose an analytical formula for calculating pressure in pump chambers. The outcome of this research can help to optimize the design parameters as well as to determine losses and impulse force causing vibration when the pump is running.